Evaluation of a quality improvement intervention for labour and birth care in Brazilian private hospitals: a protocol - Jacqueline Alves Torres; Maria do Carmo Leal; Rosa Maria Soares Madeira Domingues; Ana Paula Esteves-Pereira; Andreza Rodrigues Nakano; Maysa Luduvice Gomes; Ana Claudia Figueiró; Marcos Nakamura-Pereira; Elaine Fernandes Viellas de Oliveira; Bárbara Vasques da Silva Ayres; Jane Sandall; José M Belizán; et al. (BMC, 2018)
Abstract Background In Brazilian private hospitals, caesarean section (CS) is almost universal (88%) and is integrated into the model of birth care. A quality improvement intervention, "Adequate Birth" (PPA), based on four driving components (governance, participation of women and families, reorganisation of care, and monitoring), has been implemented to help 23 hospitals reduce their CS rate. This is a protocol designed to evaluate the implementation of PPA and its effectiveness at reducing CS as a primary outcome of birth care. Methods Case study of PPA intervention conducted in 2017/2018. We integrated quantitative and qualitative methods into data collection and analysis. For the quantitative stage, we selected a convenient sample of twelve hospitals. In each of these hospitals, we included 400 women. This resulted in a total sample of 4800 women. We used this sample to detect a 2.5% reduction in CS rate. We interviewed managers and puerperal women, and extracted data from hospital records. In the qualitative stage, we evaluated a subsample of eight hospitals by means of systematic observation and semi-structured interviews with managers, health professionals and women. We used specific forms for each of the four PPA driving components. Forms for managers and professionals addressed the decision-making process, implemented strategies, participatory process in strategy design, and healthcare practice. Forms for women and neonatal care addressed socio-economic, demographic and health condition; prenatal and birth care; tour of the hospital before delivery; labour expectation vs. real experience; and satisfaction with care received. We will estimate the degree of implementation of PPA strategies related to two of the four driving components: "participation of women and families" and "reorganisation of care". We will then assess its effect on CS rate and secondary outcomes for each of the twelve selected hospitals, and for the total sample. To allow for clinical, socio-demographic and obstetric characteristics in women, we will conduct multivariate analysis. Additionally, we will evaluate the influence of internal context variables (the PPA driving components "governance" and "monitoring") on the degree of implementation of the components "participation of women and families" and "reorganisation of care", by means of thematic content analysis. This analysis will include both quantitative and qualitative data. Discussion The effectiveness of quality improvement interventions that reduce CS rates requires examination. This study will identify strategies that could promote healthier births.